Long non-coding RNAs in plants: emerging modulators of gene activity in development and stress responses - Chen, Li (Planta, 2020)
MAIN CONCLUSION: Long non-coding RNAs modulate gene activity in plant development and stress responses by various molecular mechanisms. ABSTRACT: Long non-coding RNAs (lncRNAs) are transcripts larger than 200 nucleotides without protein coding potential. Computational approaches have identified numerous lncRNAs in different plant species. Research in the past decade has unveiled that plant lncRNAs participate in a wide range of biological processes, including regulation of flowering time and morphogenesis of reproductive organs, as well as abiotic and biotic stress responses. LncRNAs execute their functions by interacting with DNA, RNA and protein molecules, and by modulating the expression level of their targets through epigenetic, transcriptional, post-transcriptional or translational regulation. In this review, we summarize characteristics of plant lncRNAs, discuss recent progress on understanding of lncRNA functions, and propose an experimental framework for functional characterization. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00425-020-03480-5) contains supplementary material, which is available to authorized users.